Artificial intelligence in education: Effects of using integrative automated writing evaluation programs on honing academic writing instruction - Wale, Bantalem Derseh (Jurnal Cakrawala Pendidikan, 2024)
Automated writing evaluation (AWE), which is the result of educational artificial intelligence technology, is a process of scoring and evaluating learners' written texts automatically. The current study examined the effects of using integrative AWE programs on honing academic writing instruction. It also assessed students' perceptions towards using these programs. A quasi-experimental pretest-posttest two-group design was used. Test, questionnaire, focus group discussion, and teacher diary were used to collect data from 92 randomly selected participants. The experimental group students learned writing skills with Writerly and Google Docs in integration, but the control group students learned through the conventional paper and pencil feedback system. When the quantitative data were analyzed through independent samples T-test and descriptive statistics, the qualitative data were analyzed thematically. The findings revealed that using the integrated AWE programs honed academic writing instruction because there was a statistical difference between the experimental and control groups in their academic writing performance. Hence, students who learned using the integrated AWE programs honed their academic writing performance because they were able to produce essays that addressed task achievement, coherence and cohesion, lexical resource, grammatical range and accuracy. However, students who learned through the conventional method were less effective in producing quality essays. Besides, the findings also discovered that the experimental group students had positive perceptions towards using the aforementioned AWE programs because they found the programs interesting, effective, goal-oriented, and supportive. Consequently, this study recommends researchers, curriculum designers, instructional material designers, teachers, and students pay due attention to integrated AWE programs.